1999
DOI: 10.1063/1.124094
|View full text |Cite
|
Sign up to set email alerts
|

Tensile tests of ropes of very long aligned multiwall carbon nanotubes

Abstract: We have directly measured the Young’s modulus and tensile strength of multiwall carbon nanotubes by pulling very long (∼2 mm) aligned nanotube ropes with a specially designed stress-strain puller. This puller can apply an axial force to the rope and simultaneously measure the corresponding rope elongation and the change in rope resistance. The average Young’s modulus and tensile strength obtained were 0.45±0.23 TPa and 1.72±0.64 GPa, respectively, which are lower than those calculated and measured previously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
2
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(92 citation statements)
references
References 14 publications
7
79
2
4
Order By: Relevance
“…Carbon nanotubes (CNTs) [1] are based in a unique material that possesses high mechanical strength, ballistic conduction, high temperature thermal stability and high surface area [2][3][4][5]. All these extraordinary properties make them a useful material for various kinds of applications such as supercapacitors [6,7], sensors [8], field emitters [9] and for the removal of contaminants from water and gases [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes (CNTs) [1] are based in a unique material that possesses high mechanical strength, ballistic conduction, high temperature thermal stability and high surface area [2][3][4][5]. All these extraordinary properties make them a useful material for various kinds of applications such as supercapacitors [6,7], sensors [8], field emitters [9] and for the removal of contaminants from water and gases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have been shown to be an efficient adsorbent for the elimination of dibenzo-p-dioxin from contaminant water [12]. Also, they can adsorb a variety of gases and have been proven to be superior to activated carbon for the removal of dioxin1,2-dichlorobenzene from water in a wide range of pH (3)(4)(5)(6)(7)(8)(9)(10) [11,13]. Recently, X Ma et al, [14] have shown the adsorption/desorption of chlorinated compounds by pristine and thermally treated multi-walled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Any additional eccentricity present due to geometry or loading causes instability to occur at even lower loads. For example, consider a column with initial curvature corresponding to a deflection of v 0 (x); then the total deflection in the If the initial deflection is sinusoidal with amplitude a 0 given by v 0 (x) = a 0 sin(πx/l), compressive stress experienced by the column is given by (8) where S is the section modulus and P is the applied load. Equation (8) determines the compressive stress experienced by the column.…”
Section: Compressive Behavior Of Nanotube With Chemically Bonded Intementioning
confidence: 99%
“…For example, consider a column with initial curvature corresponding to a deflection of v 0 (x); then the total deflection in the If the initial deflection is sinusoidal with amplitude a 0 given by v 0 (x) = a 0 sin(πx/l), compressive stress experienced by the column is given by (8) where S is the section modulus and P is the applied load. Equation (8) determines the compressive stress experienced by the column. As this stress is higher for the same external load in the presence of an eccentricity, there is a corresponding decrease in the critical load for buckling.…”
Section: Compressive Behavior Of Nanotube With Chemically Bonded Intementioning
confidence: 99%
See 1 more Smart Citation